Evaluation of frequency of autoimmune hepatitis autoantibodies in children with type 1 diabetes - Honar, Naser (2020)
Background: Diabetes mellitus type 1 (T1DM) is one of the childhood diseases with growing prevalence. Various accompanying autoimmune diseases were seen with type 1 diabetes. The most common autoimmune diseases with T1DM are autoimmune thyroiditis and celiac disease. In some reports, autoimmune hepatitis has been reported in association with DM-1. Objectives: The aim of this study was to evaluate autoimmune hepatitis autoantibodies in children with T1DM. Materials and methods: In this crosssectional study, 202 children with T1DM were evaluated (47.5% were males and 52.5% were girls). Liver enzymes, autoimmunehepatitis related autoantibodies such as anti-nuclear antibodies (ANA), anti-smooth muscle (ASMA) and anti liver and kidney microsomal antibodies (LKM-1) were measured. Liver ultrasound was done for participants and biopsy of liver was taken for children with increased echogenicity of the liver, hepatomegaly or elevated liver enzymes. Results analyzed by statistical software spss-16, Descriptive statistics and chi-square test, paired T-TEST. Level of less than 5% was considered statistically significant. Results: In 6 patients ANA and in 4 patients (2%) ASMA was positive,1 patient was ASMA positive but ANA negative. None of the patients were Anti LKM-1 positive. 3 patients had positive ANA and ASMA, and increased liver echogenicity on ultrasound simultaneously. Histological evaluation was showed that 2 patients had findings in favor of autoimmune hepatitis. Conclusion: Auto antibodies were positive in 10 cases. ANA was positive in 6 (2.97%) of all cases. ASMA was positive in 4 (1.98%) cases. Increased echogenicity was found in 3 cases. Histological evaluation showed 2 patients had biopsy confirmed autoimmune hepatitis. AIH-2 was not seen among our cases.